Retrospective Analysis of Checkpoint Inhibitor Therapy-Associated Cases of Bullous Pemphigoid From Six German Dermatology Centers - Sadik, Christian D.; Langan, Ewan A.; Gutzmer, Ralf; Fleischer, Maria Isabel; Loquai, Carmen; Reinhardt, Lydia; Meier, Friedegund; Göppner, Daniela; Herbst, Rudolf A.; Zillikens, Detlef; Terheyden, Patrick (Frontiers in Immunology, 2021)
Immune-related adverse events (irAEs) are a class-effect of checkpoint inhibitors (CIs). One particularly serious cutaneous irAE is the development of a bullous pemphigoid (BP)-like blistering disease, driven by autoantibodies against the hemidesmosomal protein BP180, whose incidence seems to be increasing. We therefore set out to characterize the clinical and (immuno)histopathological features and treatment response of cases of BP under CI therapy collated in six German tertiary referral centers between 2014 – 2018. Thus, we identified twelve cases of BP which emerged during and/or after CI therapy. The time interval between the initiation of CI therapy and the diagnosis of BP was 3 – 74 weeks (median: 23 weeks). Age at the time of diagnosis of BP varied between 62 and 81 years (median: 76 years). The clinical presentation of the patients was diverse, but, in all cases, disease severity was rather mild compared to most cases of spontaneous BP. Only four patients met all of the immunopathological criteria recommended in the European guidelines for the diagnosis of BP. To achieve control of disease, topical corticosteroids were mostly sufficient. In 9 of 12 patients, and CI therapy could be continued. In summary, our study indicates that cases of BP under CI therapy bear several peculiarities distinguishing them from spontaneous BP. Considering the diversity of the clinical presentation of CI-induced BP and other cutaneous iRAEs, the application of existing diagnostic algorithms developed for spontaneous BP can be utilized to uncover the frequency and features of CI-induced BP and to develop optimized management algorithms.